Answer:
See below ~
Step-by-step explanation:
<u>Question 3 : (x, y - 5)</u>
- K' = (-3, 2 - 5) = <u>(-3, -3)</u>
- L' = (1, 4 - 5) = <u>(1, -1)</u>
- M' = (-1, 0 - 5) = <u>(-1, -5)</u>
- N' = (-5, -2 - 5) = <u>(-5, -7)</u>
<u></u>
<u>Question 4 : (x + 4, y + 1)</u>
- D' = (-4 + 4, 3 + 1) = <u>(0, 4)</u>
- E' = (0 + 4, 2 + 1) = <u>(4, 3)</u>
- F' = (-2 + 4, -6 + 1) = <u>(2, -5)</u>
- G' = (-6 + 4, -5 + 1) = <u>(-2, -4)</u>
A) $55.00
65 yards for $85.00 subtract
20 yards for $30.00
85-30=55
I believe it’s D. Parallel
Expand the brackets: x²+5x+6=kx+2. So x²+(5-k)x=-4.
To complete the square on the left we add ((5-k)/2)² to each side:
(x+(5-k)/2)²=((5-k)/2)²-4.
Take a look at the right hand side: when this is zero we have equal roots:
((5-k)/2)²=4, (5-k)/2=±2, 5-k=±4, k=5∓4, giving us k=1 or 9.
(5-k)/2 is 2 or -2. So if k=9, (x-2)²=0. And x=2 is the positive root.